2020
DOI: 10.1103/physreve.101.063005
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation screening in crystals with spherical topology

Abstract: Whereas disclination defects are energetically prohibitive in two-dimensional flat crystals, their existence is necessary in crystals with spherical topology, such as viral capsids, colloidosomes, or fullerenes. Such a geometrical frustration gives rise to large elastic stresses, which render the crystal unstable when its size is significantly larger than the typical lattice spacing. Depending on the compliance of the crystal with respect to stretching and bending deformations, these stresses are alleviated ei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…(4) vanish upon integration over the entire surface. The optimal dislocation flux Φ can be computed, for a given surface, by minimizing the energy E S [25], although all our results still hold qualitatively under the assumption of lit-tle to no screening (i.e. Φ = 0).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…(4) vanish upon integration over the entire surface. The optimal dislocation flux Φ can be computed, for a given surface, by minimizing the energy E S [25], although all our results still hold qualitatively under the assumption of lit-tle to no screening (i.e. Φ = 0).…”
mentioning
confidence: 74%
“…Following Ref. [25], we express η in terms of a discrete set of "seed" disclinations, coupled with a continuous distribution of screening dislocations. This yields:…”
mentioning
confidence: 99%
“…We note that our work is in contrast with the literature where the deformed shape of the elastic sheet is predetermined and a defect configuration is sought which is compatible with the shape morphology. 4,5,[15][16][17] These frozen topographies appear when the surface is backed by a fluid substrate as is the case in the problems associated with the determination of virus shapes. 4 On the contrary, we assume that the position of the defect is fixed and allow the elastic surface to develop any arbitrary shape.…”
Section: Introductionmentioning
confidence: 99%
“…Reasoning along similar lines, one also expects that as R increases, locally different tessellations can be patched together at only moderate cost, as the density of structural defects arising in the patching decreases with size [30]: this results in an increased likeliness of observing amorphous structures. Additionally, as in scar screening [50][51][52] in two-dimensional spherical crystals, large strains introduced by the topologically required defects could be alleviated by the proliferation of excess dislocations with null topological charge when R significantly exceeds the lattice spacing [53]. Correspondingly, by systematically starting from different initial conditions for a given set of parameters, we found that for sufficiently large R amorphous states are either metastable [30] or even thermodynamically stable, in which case their free energy is lower than that of any of the quasicrystal phases observed in our simulations (see Fig.…”
mentioning
confidence: 99%